GHPSS Multicenter Italian Survey: Smoking Prevalence, Knowledge and Attitudes, and Tobacco Cessation Training among Third-Year Medical Students. Issue 1 (January 2013) - Saulle, Rosella; Bontempi, Claudio; Baldo, Vincenzo; Boccia, Giovanni; Bonaccorsi, Guglielmo; Brusaferro, Silvio; Donato, Francesco; Firenze, Alberto; Gregorio, Pasquale; Pelissero, Gabriele; Sella, Alberto; Siliquini, Roberta; et al.
Aims and background: Healthcare professionals have an important role to play both as advisers – influencing smoking cessation – and as role models. The aims of this study were to examine smoking prevalence, knowledge and attitudes among Italian university students attending medical schools using the Global Health Professions Student Survey (GHPSS) approach. Methods and study design: A multicenter cross-sectional study was conducted among University students of 9 Italian medical schools (age ranging between 19 and 29 years). The GHPSS questionnaire was self-administered. A logistic regression model was used to identify possible factors associated with tobacco smoking status. Data were analyzed with the software SPSS 19.0 for Windows. Results: Seven hundred thirty medical students (response rate 100%) were enrolled. The prevalence of current smokers was 20.4% (males 22.4%, females 19.1%). Of the total sample, 87.7% believed that health professionals should receive specific training in techniques to quit smoking, and 65% believed that health professionals had a role in giving advice or information about smoking cessation. However, 89.4% answered that they had not received specific training on smoking cessation techniques. Multivariate analysis showed that students belonging to universities in southern Italy were more likely to be smokers (OR = 2.00; 95% CI: 1.03–3.97). Conclusions: This Italian multicenter survey found that one fifth of future medical doctors are smokers. There is a need to adopt a standard undergraduate curriculum containing comprehensive tobacco prevention and cessation training to improve their effectiveness as role models.